2014
DOI: 10.1080/13102818.2014.901669
|View full text |Cite
|
Sign up to set email alerts
|

Examination of extremely low frequency electromagnetic fields on orthodontic tooth movement in rats

Abstract: The purpose of this study was to evaluate whether 50 Hz extremely low frequency electromagnetic fields (ELF-EMFs) affect the amount of orthodontic tooth movement in rats. The experiments were performed on 18 male Sprague-Dawley rats. The rats were randomly divided into three groups (n = 6): cage-control (Cg-Cnt) group (n = 6); sinusoidal electromagnetic field (SEMF) group (n = 6); and pulsed electromagnetic field (PEMF) group (n = 6). In SEMF and PEMF groups, rats were subjected to 1.5 mT EMF exposure eight ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…46 Studies on a rat model have shown that the support of active orthodontic elements operating with a force of about 20 g, both using a PEMF of 1.8 mT (or 1.5 mT) and a Nd-Fe-B magnet (neodymium), increases the distance a tooth can be moved. 47,48 Stark and Sinclair and Showkatbakhsh et al also confirmed the accelerating action of PEMF. 32,49 The clinical trial by Showkatbakhsh et al, assessed the distalization of the canine after 1 st premolar extraction, using a removable PEMF-generating device with an intensity of 0.5 mT and a frequency of 1 Hz.…”
Section: Electromagnetic Fi Eldssupporting
confidence: 51%
See 1 more Smart Citation
“…46 Studies on a rat model have shown that the support of active orthodontic elements operating with a force of about 20 g, both using a PEMF of 1.8 mT (or 1.5 mT) and a Nd-Fe-B magnet (neodymium), increases the distance a tooth can be moved. 47,48 Stark and Sinclair and Showkatbakhsh et al also confirmed the accelerating action of PEMF. 32,49 The clinical trial by Showkatbakhsh et al, assessed the distalization of the canine after 1 st premolar extraction, using a removable PEMF-generating device with an intensity of 0.5 mT and a frequency of 1 Hz.…”
Section: Electromagnetic Fi Eldssupporting
confidence: 51%
“…Dogru et al performed an experiment on rats comparing a PEMF to a sinusoidal field. 48 In both cases, they observed positive effects. However, the authors pointed out that due to differences in size and physiology, predicted results on the human body should be extrapolated with caution.…”
Section: Electromagnetic Fi Eldsmentioning
confidence: 87%
“…The active and passive tooth apparatus were designed and applied to obtain experimental orthodontic tooth movement in this study 35 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the studies that were done on animals, shown that the application of low-intensity pulsed ultrasound caused an acceleration of the process that lead to new bone formation. The pulsed electromagnetic fields (PEMFs) application influence bone metabolism [3]. Several studies demonstrated that electromagnetic fields accelerate the bone formation.…”
Section: Physical Stimulimentioning
confidence: 99%